Combining Ability, Gene Action And Heterosis In Sesame - Elizabeth George (Department of Plant Breeding, College of Agriculture, 1989)
Evaluation of six parents and fifteen hybrids of sesame were undertaken in the uplands of Vellayani for combining ability, gene action and heterosis. The six parents were chosen from twentythree sesame verities based on their general performance, which were then crossed in all possible combinations, excluding reciprocals, to get fifteen hybrids. Eleven characters, which included yield and yield attributes were studied. Significant differences were observed among the twentyone treatments for all the characters studied, except for days to mature. Combining ability analysis was carried out based on Method 2 under Model I as suggested by Griffing (1956). The variance due to specific combining ability was significant and higher in magnitude than general combining ability variance for all the characters. It was seen that the varieties S.8 and VS.27 were the best general combiners and the cross combinations CO.1 x VS.27, VS.27 x K.1 and CO.1 x S.8 were the best specific combinations for yield and yield attributes. The important yield attributes and yield were conditioned by significant g.c.a and s.c.a variances suggesting the importance of additive and non-additive gene action in combining the inheriance of these characters. Non- additive gene action was found to be predominant for all the characters studied. Heterosis percentage was calculated over mid, better and check parental values. Positive heterosis was noticed for all the characters in general and maximum vigour was manifested for the characters capsule number per plant and seed yield. Heterosis in seed yield was reflected through heterosis in yield components. In the present study, a near perfect positive correspondence was observed between s.c.a and the extent of heterosis. The varieties S.8 and VS.27 and the cross combinations CO.1 x VS.27, VS.27 x K.1 and CO.1 x S.8 can be further exploited while framing future breeding programmes.